Preliminary Design of a 6-Seater Electric Aircraft - Chandra, C; Khan, M; Putri, T; Alexsoh, W; Moelyadi, M A; Amalia, E (International Journal of Aviation Science and Engineering - AVIA, 2023)
A more sustainable and eco-friendly aircraft is needed for the near future, but current electric aircraft technology (e.g., electric motors and batteries) is still lacking compared to its fossil-fuel- based counterparts. To support the effort for fully electric aircraft maturity, an electric aircraft up to its preliminary design stage is developed using various analytical and software-based analyses with the target of fulfilling a set of design requirements and objectives for a 5000 kg MTOW 6-seater fully electric aircraft. The results of the aircraft preliminary design yield that overall, the aircraft fulfills all the requirements and most of the objectives. The design itself can still be further developed through optimization, re-evaluation, future studies, and upcoming technologies.